Preventing Shift Work Disorder in Shift Health-care Workers - Gabriele d'Ettorre; Vincenza Pellicani (Elsevier, 2020)
The occurrence of the shift work disorder (SWD) in health-care workers (HCWs) employed in 24/7 hospital wards is a major concern through the world. In accordance with literature, SWD is the most frequent work-related disturb in HCWs working on shift schedules including night shift. In agreement with the Luxembourg Declaration on workplace health promotion (WHP) in the European Union, a WHP program has been developed in a large Hospital, involving both individual-oriented and organizational-oriented measures, with the aim to prevent the occurrence of SWD in nurses working on shifts including night shift. The objective assessment of rotating shift work risk and the excessive sleepiness were detected before and after the implementation of the WHP program, by using the Rotating Shiftwork-questionnaire and the Epworth Sleepiness Scale. The findings of this study showed the effectiveness of the implemented WHP program in minimizing the impact of shift work on workers' health and in preventing the misalignment between sleep-wake rhythm and shift working.